Pemanfaatan Media Soasial Sebagai Upaya Mengenalkan Taman Banjarsari Agro Comunity (BAC) - Dyah Rakhwati Tri Atmayanti; Nur Salam; Muhammad Agil Haikal; Machrus Ali; Putri Bahiyyah (Jurnal Pengabdian Masyarakat Universitas Darul Ulum, 2023)
One of the problems in the management of the Banjarsari Agro Community Park (BAC) located in Bajarsari Village, Bandarkedungmulyo District, Jombang Regency is the lack of understanding and maximizing social media that currently exists for the development process of the Banjarsari Village Tourism Park which is currently in the development stage. So far, the spread of these tourist attractions has been mostly through word of mouth or communities who have visited BAC. The hope is that in the future, with managers who operate and this tourist spot has social media, its existence will be increasingly recognized by people and its development will be faster.